Enhanced long-term organics and nitrogen removal and associated microbial community in intermittently aerated subsurface flow constructed wetlands. (August 2016) - Fan, Jinlin; Zhang, Jian; Guo, Wenshan; Liang, Shuang; Wu, Haiming
Graphical abstract: Highlights: The long-term enhanced treatment performance in aerated SSF CW was evaluated. The high removal efficiency of COD (95%), NH4 + -N (96%) and TN (85%) was detected. Intermittent aeration significantly enhanced the abundance of nitrifying bacteria. Abstract: The long-term enhanced removal efficiency of organics and nitrogen in subsurface flow constructed wetlands (SSF CWs) with and without intermittent aeration for decentralized domestic wastewater was evaluated, and the function of intermittent aeration on microbial community was also investigated in this study. The high and long-term 95.6% COD, 96.1% NH4 + -N and 85.8% TN removal efficiencies were achieved in experimental intermittently aerated SSF CW compared with non-aerated SSF CW. Aerated SSF CWs also exhibited the excellent removal performance when comparatively comparing with other strategies and techniques applied in CWs. In addition, fluorescence in situ hybridization (FISH) analysis revealed that associated microbial abundance significantly increased owing to intermittent aeration. These results indicated intermittent aeration CWs might be an effective and sustainable strategy for wastewater treatment in rural areas, but require further full-scale investigation in future.